Aging and Senescence of Dental Pulp and Hard Tissues of the Tooth - Maeda, Hidefumi (Frontiers in Cell and Developmental Biology, 2020)
The ability to consume a meal using one’s own teeth influences an individual’s quality of life. In today’s global aging society, studying the biological changes in aging teeth is important to address this issue. A tooth includes three hard tissues (enamel, dentin, and cementum) and a soft tissue (dental pulp). With advancing age, these tissues become senescent; each tissue exhibits a unique senescent pattern. This review discusses the structural alterations of hard tissues, as well as the molecular and physiological changes in dental pulp cells and dental pulp stem cells during human aging. The significance of senescence in these cells remains unclear. Thus, there is a need to define the regulatory mechanisms of aging and senescence in these cells to aid in preservation of dental health.